2018
DOI: 10.3390/su10103719
|View full text |Cite
|
Sign up to set email alerts
|

Using Local Agroecological Knowledge in Climate Change Adaptation: A Study of Tree-Based Options in Northern Morocco

Abstract: Communities in northern Morocco are vulnerable to increasing water scarcity and food insecurity. Context specific adaptation options thus need to be identified to sustain livelihoods and agroecosystems in this region, and increase the resilience of vulnerable smallholders, and their farming systems, to undesired effects of social-ecological change. This study took a knowledge-based systems approach to explore whether and how tree-based (i.e., agroforestry) options could contribute to meeting these adaptation n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 12 publications
0
33
0
7
Order By: Relevance
“…In the general context of global climate changes, the agricultural sector seems to be one of the most severely affected. The vast majority of previously developed studies indicated important impacts of climate changes on different crops, especially in developing countries [1][2][3][4]. Under these changing conditions, the geographical position and local factors of an area are expected to have a crucial impact on agriculture, based on the current climatic characteristics, soil properties, resources of the area, existing infrastructure, and direction of change [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the general context of global climate changes, the agricultural sector seems to be one of the most severely affected. The vast majority of previously developed studies indicated important impacts of climate changes on different crops, especially in developing countries [1][2][3][4]. Under these changing conditions, the geographical position and local factors of an area are expected to have a crucial impact on agriculture, based on the current climatic characteristics, soil properties, resources of the area, existing infrastructure, and direction of change [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A key challenge limiting sustainable intensification of agriculture is that smallholder farming systems are heterogeneous and dynamic, not only in their biophysical context (including soils) but also in terms of famer circumstances, production objectives and socio-technical conditions (Kmoch et al, 2018;Tittonell et al, 2005;Vanlauwe et al, 2014). Despite this heterogeneity in smallholder farming systems, conventional soil management and land restoration approaches in Rwanda have prescribed a narrow set of soil management options, often informed by coarse-resolution assessments.…”
Section: Introductionmentioning
confidence: 99%
“…While bottom-up approaches are important for ensuring community engagement, top-down support can help to design and implement more rigorous experimental efforts that can be replicated and upscaled [87]. As part of such a mixed-methods integrative approach, local qualitative inquiries can help stakeholders prioritize quantitative investigations on broader scales [89].…”
Section: Integration Of Top-down and Bottom-up Approaches Is Necessarmentioning
confidence: 99%